A methods engineering study on Precision Crestec, Inc. - Mananquil, Iris Mae; Ramiscal, Edgar Allan S.; De Villa, Ommaric L. (Diliman, Quezon City College of Engineering, 2004)
A methods engineering study was performed on Precision Crestec Incorporated, a manufacturing corporation that provides layout services and manufactures folding cartons, labels, manuals, brochures, and other point of purchase materials with offset printing. It is a dynamic organization that is highly competitive in the global market, continuing to provide products for top corporations both locally and internationally. The study was focused on the company's plant that manufactures printer manuals and boxes. The primary problems that the investigators identified in the plant revolve around materials, manufacturing methods, work environment and equipment, that all lead to high costs and much product rejects. Ineffective material planning has lead to inadequate raw materials from the foreign suppliers, specifically the paper for printing, which in turn leads to alternative sourcing of lower grade paper. These lower grade materials in turn lead to occasional damage to the company's machinery as well as added labor costs since they have to be manually processed before being fed to the press. The company also just recently purchased a second hand machine for binding and cutting the manuals. And since it is just new, its consumable parts have not yet been established, thus when the machine broke down, repairing and replacing the damaged parts was very demanding. Investigators observed ineffectiveness in the supervision and implementation of the company's work instructions and methods, detrimental work environment both for the health of the worker and their products, and inferior manual work methods that lead to bottlenecks in their operations. Slower progress in the work of the manual workers especially in the pasting area of the plant, have been observed to also be due to the avoidable delays and constant distractions from coworkers and colleagues. To address these primary problems, the investigators have developed short term, middle term and long term solutions. The short term solutions include tackling problems in the work environment like providing proper color and lighting to the workstations and providing anti-fatigue mats for those workers assigned for inspection. For the case of ineffective supervision of the workers, the investigators propose putting up divisions in the pasting area and suggest that the supervisors accurately check the actual time and output of the workers, and not entirely rely on work monitoring reports. Recommendations for the machine breakdowns include contacting the previous owner of their second hand machine and acquire its manuals to be able to establish its consumer parts. These solutions have durations that last from two days to two months and would have a cumulative cost of approximately Php1,000 aside from clerical costs, communication costs, for contacting the owner the second hand machine, and training costs that would very much vary. Middle term solutions include conducting operations research to establish the optimal buffer for their supplies of raw materisl. Also, the investigators recommend that mechanical engineers study their machines further to prevent breakdowns or easily repair and replace their parts. For the case of the work environment and workstations, the long term project is the installation of exhaust and industrial fans and providing adjustable stools to the manual workers. Standards times should be reevaluated while standard methods established especially for the workers in the pasting area which is a bottleneck operation. These solutions span from two weeks to four months and cost approximately Php10,000 except for the operations research which would incur an uneven study cost. Finally the long term projects the investigators propose are the computerization of the company's inventory system for more effective tracking and channeling of their resources as well as the automation of the gluing process, because it is the only operation which is manually performed. These projects would cost around Php1,100,000 and would span from three to nine months for their implementation. All these project proposals are still subject to implementation, evaluation and further analysis both for added productivity and development of the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Precision Estec Incorporated; Paper industry; Systems analysis